Thrombus-in-Transit Entrapped in a Partially Ligated Left Atrial Appendage - Farideh Roshanali; MohammadHossein Mandegar; Bahieh Moradi (Journal of Tehran University Heart Center, 2015)
A 54-year-old man referred to our center with Barlow’s disease and severe mitral regurgitation. He had atrial fibrillation (AF) rhythm, with a mildly enlarged left atrium (LA). Transesophageal echocardiography (TEE) showed no clot in the LA and LA appendage; there was only mild spontaneous echo contrast in the LA appendage. The patient underwent mitral valve repair and the Maze operation, during which the LA appendage was ligated with the double suture technique. He was discharged from the hospital in good condition and in sinus rhythm. He was recommended Warfarin and PT control.